If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = 6 + 2z Reorder the terms: 3 + 4x = 6 + 2z Solving 3 + 4x = 6 + 2z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 6 + -3 + 2z Combine like terms: 3 + -3 = 0 0 + 4x = 6 + -3 + 2z 4x = 6 + -3 + 2z Combine like terms: 6 + -3 = 3 4x = 3 + 2z Divide each side by '4'. x = 0.75 + 0.5z Simplifying x = 0.75 + 0.5z
| 256*a*b*c*d/192*b*c*d | | 5z+22-15z= | | -5x+23y=-13 | | 250x=45000 | | 250x=4500 | | (3x+4)*(x-6)+24=0 | | 23x+5y=-17 | | 500b=27500 | | (6x+4)=(8x+6) | | (2x-9)=3x-12 | | 250x=25000 | | 500b=25000 | | 5x-4+6-4x=2x-7 | | (2x-3)*(x+4)=-12 | | 250x=15000 | | 32x-8x^2=0 | | 3.2x-8x^2=0 | | 9/x+6+4/x-6 | | 250x=30000 | | r(r-4)=21 | | 500b=20000 | | 14x^2-1.5x=0 | | 4x-(3x+7)=-4 | | 1.5x-14x^2=0 | | 6(x-.8)-.2(5x-4)=8 | | -2x^2+0.5x=0 | | 14(8b+4)=12(1+10b)-12b | | 12x^2-28x=0 | | 12x^2-28=0 | | x/6=x/18+2/3 | | 2x+166=8x-8 | | 4x-4+3x+6=4x-1 |